KESADARAN PENTINGNYA MENABUNG SEJAK USIA DINI DI SEKOLAH DASAR NOMOR 040/ XI DESA KOTO LIMAU MANIS - Sumanti, Eva; Nilda, Elvi; Syarif, Dafiar (Institut Agama Islam Negeri Kerinci, 2021)
This service aims to instill a culture of saving from an early age in children, as it is known that saving is a form of investment that must be taught to the nation's next generation. This research used a direct outreach approach to Elementary School Number 040/XI Koto Limau Manis Village students. This service results in students knowing the importance of saving from an early age to create a culture of saving until adulthood.